Benign prostatic hyperplasia and periodontitis - YANG Shisong; ZHU Cong; QIAN Xinhang; HOU Junqing; FANG Cheng (Yixue xinzhi zazhi)
Benign prostatic hyperplasia and periodontitis are common chronic diseases in middle-aged and elderly people, with many common risk factors and pathogenesis. Epidemiological studies have found that periodontitis can increase the risk of prostate hyperplasia, however, its mechanism is not clear yet. This article reviews the current research status and possible mechanisms of the correlation between periodontitis and benign prostatic hyperplasia, aiming to provide a basis and ideas for future clinical diagnosis, treatment, and related research.